Differences Of Penabuh Authority In The Interpretation Of Musical Patterns Between Composition In The Middle And New Era Of Balinese Karawitan - Ardana, I Ketut; Palupi, Warananingtyas; Horta, Miguel (Al-Makki Publisher, 2024)
This study articulates the authority of penabuhs in interpreting musical patterns because it has never been elaborated on in any research topic. It is vital because penabuhs have a considerable role in the existence of Balinese gamelan from time to time. That is, no Balinese gamelan exists without the involvement of penabuhs in it. The penabuh's authority was examined from two eras of Balinese gamelan development, which aims to determine the differences in penabuh's authority in the two eras, namely the middle and new eras. Therefore, research uses an ethnographic approach. Data collection was conducted through interviews with Balinese gamelan penabuhs. Gajah Nongklang and Jaya Semara are data samples representing the composition of the Middle and New Eras. Aims to identify how changing times, both in the middle era and the new era, influence the way musicians interpret and execute musical patterns in Balinese karawitan. The study results concluded that the authority of penabuhs in the middle era was more significant than in the new era. The middle-era penabuhs had a role in interpreting melody, rhythm, tempo, and dynamics. Therefore, penabuhs are also consumed as composers. In the new era, on the other hand, the authority to interpret these patterns is the composer.